Creativity and Critique in Digital Learning and Teaching: Insights for Learning Design in Business and Law (Springer Nature, 2025)
This open access edited collection is aimed at educators, student services staff, and university management. It is timely in adopting a forward-facing view of various aspects of digital teaching and learning in business and law and provides a vital resource for those designing, managing or thinking about digital learning in both fields.